2002
DOI: 10.1046/j.1365-246x.1999.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass accumulation rates in Asia during the Cenozoic

Abstract: Summary This work establishes estimates of mass accumulation rates in 18 mostly offshore sedimentary basins in Asia since the beginning of the Cenozoic, ≈ 66 Ma. The estimates were derived from isopach maps, cross‐sections and drill holes or stratigraphic columns assuming regional similarity of the strata. Average solid phase volumes and accumulation rates were calculated for nine epochs approximately corresponding to geological periods: Palaeocene ( ≈ 66–58 Ma), Eocene ( ≈ 58–37 Ma), Oligocene( ≈ 37–30 and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
221
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(238 citation statements)
references
References 83 publications
(206 reference statements)
14
221
2
1
Order By: Relevance
“…Furthermore, compilations of global sediment budgets indicate that erosion rates since the initiation of Northern Hemispheric Glaciation are much elevated compared to those before ca. 3 Ma (Métivier et al, 1999;Zhang et al, 2001). It should also be realized that modern rivers are not in equilibrium, but still adjusting to climate change after the Last Glacial Maximum (ca.…”
Section: Erosional Destruction Of Cratonic Crust During the Cenozoicmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compilations of global sediment budgets indicate that erosion rates since the initiation of Northern Hemispheric Glaciation are much elevated compared to those before ca. 3 Ma (Métivier et al, 1999;Zhang et al, 2001). It should also be realized that modern rivers are not in equilibrium, but still adjusting to climate change after the Last Glacial Maximum (ca.…”
Section: Erosional Destruction Of Cratonic Crust During the Cenozoicmentioning
confidence: 99%
“…We also make a correction for major carbonate masses, although close to the deltas of major rivers this is rarely a significant issue within the errors of the general estimate. In some delta and submarine fan systems there has been significant seismic analysis performed and sediment volume estimates already made (e.g., many of the Asian delta systems (Métivier et al, 1999;). In these cases we simply use the published volumes for Cenozoic sediment masses.…”
Section: Erosional Destruction Of Cratonic Crust During the Cenozoicmentioning
confidence: 99%
“…A late Cenozoic increase in sedimentation rates has been documented in sedimentary basins occurring in widely varying tectonic settings around the world, suggesting that the associated increase in erosional flux is climatically controlled (Kuhlemann et al, 2002;Métivier et al, 1999;Molnar, 2004;Zhang et al, 2001). A contrasting view has, however, been expressed by Raymo and Ruddiman (1992), who suggested that, rather than resulting from it, increased uplift and erosion rates control late-Cenozoic climate change through increased atmospheric CO 2 drawdown by weathering reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Such a perspective is therefore still far from clear promoting us to pursue further studies of the molecular phylogenetics of the sisorid catfishes. It has long been recognized that paleo-drainages of major continental East Asian Rivers, draining the south-eastern Tibet plateau margin, differed markedly from their current drainage patterns (Brookfield, 1998;Clark et al, 2004;Gregory, 1925;Gregory and Gregory, 1923;Hallet and Molnar, 2001;Métivier et al, 1999;Seeber and Gornitz, 1983;Zeitler et al, 2001). In a recent study, Clark et al (2004) suggested that these rivers were once tributaries to a single southward flowing system, which drained into the South China Sea (Fig.…”
Section: Introductionmentioning
confidence: 99%